Pembelajaran Mandiri Aplikasi Enterprise Resource System: Studi Kasus pada Aplikasi SAP – Modul Sales and Distribution - Johan, Johan (Bina Nusantara University, 2013)
ERP (enterprise resource planning) is a solution needed by companies to assist the integration of all functional areas. A self-learning media of ERP system is needed for the successful use which is highly depended on the users mastery. The learning media must be flexible to time and place. Therefore, this research creates a self-learning application for ERP system based on a case study on SAP application. SAP is an ERP-based solution widely used by medium to large companies. The method used are data collection, analysis on running business processes and the identification of information needs, followed by the application design. Identificationof system requirements uses Flash CS5 Action Script 3.0. The result achieved in this research is a multimediabased learning tool which assists training for trainers and trainee and facilitates trainee supervision during training. The learning tool is found helpful in self learning process.